Effect of partially hydrolyzed synbiotic formula milk on weight gain of late preterm and term infants—a multicenter study - Sahin, Suzan; Buyuktiryaki, Mehmet; Okur, Nilufer; Akcan, Abdullah Baris; Deveci, Mehmet Fatih; Yurttutan, Sadik; Gunes, Sezgin; Anik, Ayse; Ozdemir, Ramazan; Uygur, Ozgun; Oncel, Mehmet Yekta (Frontiers in Pediatrics, 2023)
Introduction: Data on the effectiveness of hydrolyzed infant formula containing both pre-and probiotics (synbiotic formula) on growth of infants is still scarce. This retrospective study was designed to evaluate the effect of a partially hydrolyzed synbiotic formula on growth parameters and possible occurrence of major gastrointestinal adverse events or morbidities in infants born via cesarean section (C-section) delivery. Methods: C-section delivered term and late preterm infants who received either partially hydrolyzed synbiotic formula, standard formula or maternal milk and followed at 7 different hospitals from 5 different regions of Turkey, during a one-year period with a minimum followup duration of 3 months were evaluated retrospectively. All the included infants were evaluated for their growth patterns and any kind of morbidity like diarrhea, constipation, vomiting, infection or history of hospitalization. Results: A total of 198 infants (73 in human milk, 61 in standard formula and 64 in partially hydrolyzed synbiotic formula) could reach final analysis. The groups were similar regarding their demographic and perinatal characteristics. No difference was observed in between three groups regarding gastrointestinal major side effects. Growth velocities of the infants in human milk and partially hydrolyzed synbiotic formula during the first month of life were similar whereas weight gain of infants in the standard formula group was significantly less then these two groups (p<0.001). Growth velocities were similar in three groups between 1 st -3 rd months of age. Discussion: A partially hydrolyzed synbiotic formula could provide a better weight gain in latepreterm and term infants who were delivered via C-section delivery compared to the standard formula during the first month of life. This weight gain was similar to the infants receiving exclusively human milk. This difference was not observed in length and head circumference gain. No difference was observed in any of the parameters during the 1 st -3 rd months of age. Specially formulated partially hydrolyzed synbiotic formulas may reverse at least some of the negative impacts of C-section delivery on the infant and help to provide a better growth especially during the early periods of life.